Implant placement and immediate loading in aesthetic zone- A report of three cases - Vijay Deshmukh; Hiral Jhaveri; Amrita Kishore (Wolters Kluwer Medknow Publications, 2009)
Single teeth replaced by implants in the aesthetic zone are one of the most challenging situations faced by a clinician. Recent studies have encouraged a progressive shortening of the healing period for single-tooth implants with immediate implantation and immediate loading being proposed for the aesthetic zone in the maxilla. The present report describes three cases with single tooth replacement in the anterior maxillary region by implant therapy with flapless technique followed by immediate provisionalization of the implant with all-ceramic crown. The patients exhibited no clinical or radiologic complications 1 year after loading. Implant placement and immediate loading of single tooth can provide an attractive treatment option in the aesthetic zone. Careful assessment must be made of mucosal and bone volumes in relation to implant placement for optimum aesthetic outcome.